If They Knew Then What We Know Now, Why Haven't Things Changed? An Examination of District Effectiveness Research - Anderson, Erin; Young, Michelle Diane (Frontiers in Education, 2018)
For over 30 years, proponents of district effectiveness have promoted a fairly consistent set of key practices to enable district-wide improvement; yet, the state of district effectiveness has changed very little. This paper examined three decades of research on district practices associated with school performance and student achievement to gain a better understanding of the utility of this research-base in fostering district improvement. This study used a sample of 98 peer reviewed journal articles, reports, books and book chapters, and working papers to explore (1) patterns in the research design by categorizing research types and reporting sampling methods, such as sample size and sample type; (2) patterns of district characteristics in the sample by looking at types of districts, documenting urbanicity, looking at student enrollment, and discussing the socio-economic status of the student population; and (3) patterns of authorship and research productivity by surveying the concentration of authors and determining the proliferation of data sets. Importantly, this analysis found the research base on district practices to be too limited to serve as a comprehensive guide for stakeholders at various levels of the system seeking to support district improvement. We argue that the research base is too narrow and only applicable to certain types, locations, and size of districts. Furthermore, most of the studies take place in urban districts undergoing reform, which is not generalizable to most of the districts in the United States-largely smaller, rural districts. Lastly, when you consider the authorship of these studies, the base gets even narrower, as many authors produced multiple papers from one research study; one the other hand, the remaining studies seem to be from scholars who do not consider district effectiveness as their primary research interest. In order to better understand what district practices are most effective at promoting the ability of a district to achieve the mission of delivering high quality and equitable educational experiences for each student, we make recommendations for future research.